Usefulness of the subunit principle in nasal reconstruction - Cerci,Felipe Bochnia (2017)
Abstract The subunit principle in nasal reconstruction proposed the concept of reconstructing the specific topographic subunits that were identified as dorsum, tip, columella, the paired alae, sidewalls, and soft triangles. In patients with more than 50% of subunit loss, removing the remaining portion of the subunit and reconstructing the entire subunit may yield better results. The placement of incisions along the borders of the subunits minimizes scar lines. Furthermore, as trapdoor contraction occurs, the entire restored subunit bulges in a way that mimics the normal contour of a nasal tip, dorsum or ala. Two cases of nasal reconstruction that followed this important principle are described.